(untitled) (Zoological Records and Reviews, 2021)
The genus Rana (Linnaeus, 1758) in South India has historically been subject to extensive taxonomic confusion, with numerous species described, synonymised, and re-elevated across nearly two centuries of systematic work. Despite recent molecular revisions of the broader Ranidae family, South Indian Rana diversity remains incompletely characterised, with several morphologically diagnosable populations lacking formal species status. This study presents a systematic revision of the genus Rana in South India based on integrative analysis of morphometric data (22 variables), qualitative external characters, and mitochondrial sequence data (16S rRNA and cytochrome b) from 318 individuals spanning 24 sampling localities across the Eastern Ghats, Western Ghats, and Deccan Plateau. Bayesian and maximum likelihood phylogenetic analyses consistently recover five well-supported South Indian Rana lineages, two of which are herein recognised as valid species following integrative assessment: Rana ghatsensis sp. nov. from the moist deciduous forests of the Eastern Ghats, and Rana deccanensis sp. nov. from plateau grassland habitats. Updated synonymies, a revised dichotomous identification key, and complete morphometric diagnoses are provided for all recognised South Indian Rana taxa. Four additional populations representing potential undescribed diversity are flagged for priority investigation. Habitat assessments indicate that three of the five lineages face significant range contraction due to agricultural expansion and forest fragmentation.